(untitled) (Global Journal of Human-Social Science, 2025)
This paper explores the representation of caste discrimination and subaltern consciousness in Mulk Raj Anand s seminal novel Untouchable 1935 and Ashutosh Gowariker s Bollywood film Lagaan 2001 Through a humanistic lens the study analyzes how both texts critique the entrenched caste hierarchies of Indian society Drawing on subaltern theory and postcolonial frameworks the paper argues that while Untouchable presents a direct and emotionally charged portrayal of Dalit oppression Lagaan uses metaphor and cinematic spectacle to raise subtle questions about caste unity and resistance under colonial rule